2012
DOI: 10.1007/s10140-012-1029-0
|View full text |Cite
|
Sign up to set email alerts
|

Utility of ultrasound for evaluating the appendix during the second and third trimester of pregnancy

Abstract: This study aims to retrospectively evaluate the right lower quadrant ultrasounds in women presenting during the second or third trimester of pregnancy for the frequency of appendix visualization and accuracy in diagnosing appendicitis. Institutional Review Board approval was obtained for this Health Insurance Portability and Accountability Act-compliant study. We reviewed imaging records from 99 consecutive pregnant women from 2001 to 2011 who presented during the second (≥14 weeks gestation) or third trimeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 34 publications
2
27
0
14
Order By: Relevance
“…The reported diagnostic performance of US for detecting appendicitis in pregnancy varies widely in the literature [13]. Sensitivity of 20%e46.1% [5,13,15,16] and specificity of 95.4%e100% [5,15,16] is reported. However, US seems to be of limited utility during pregnancy due to the high rate of non-visualization of the appendix (88%e97%) [13,15].…”
Section: Discussionmentioning
confidence: 97%
“…The reported diagnostic performance of US for detecting appendicitis in pregnancy varies widely in the literature [13]. Sensitivity of 20%e46.1% [5,13,15,16] and specificity of 95.4%e100% [5,15,16] is reported. However, US seems to be of limited utility during pregnancy due to the high rate of non-visualization of the appendix (88%e97%) [13,15].…”
Section: Discussionmentioning
confidence: 97%
“…28 Several studies have reported non-visualization of the appendix in a large percentage of pregnant women with suspected appendicitis. [29][30][31][32][33] However, in a review of studies on the value of ultrasound diagnostics during appendicitis in pregnancy, sensitivity ranged from 67 to 100% and specificity of 83 to 96%, compared with the general population, in which sensitivity and specificity were 86 and 96%, respectively. 34 Several factors influence the performance of ultrasound diagnosis of appendicitis in pregnancy, including gestational age, body mass index (BMI), and most importantly, the training and experience of the examiner.…”
Section: 28mentioning
confidence: 99%
“…It is reported that USG has a high rate of non-visualization of the appendix during pregnancy. 12 Similarly, Aggenbach et al reported, in a study that evaluated 21 pregnant patients who underwent appendectomy, 75% of non-visualized appendix on USG. 13 Our result was inconsistent with this study, since we found non-visualized appendix in only 45.7% of the pregnant patients, less than the previously reported data.…”
Section: Discussionmentioning
confidence: 90%